2017
DOI: 10.1016/j.ekir.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Transition of End-Stage Kidney Disease in Oman

Abstract: IntroductionThe number of persons receiving renal replacement therapy (RRT) is estimated at more than 2.5 million worldwide, and is growing by 8% annually. Registries in the developing world are not up to standards compared to the United States Renal Data System (USRDS). Herein we examine the causes, progression, and magnitude of end-stage kidney disease (ESKD) over 3 decades in Oman.MethodsWe examined ESKD data from 1983 to 2013. Data from 1998 to 2013 were obtained through an Information Management System. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 34 publications
2
33
0
Order By: Relevance
“…Commercial transplant tourism accounts for almost 10% of the total transplants worldwide per year (Akoh, 2012). The present authors have previously reported that commercial transplant tourism accounts for almost 75% of RTX in Oman (Al Ismaili et al, 2017). In the present study, it was found that all of the commercial transplants in cases diagnosed with IFI were performed at various locations in Pakistan.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Commercial transplant tourism accounts for almost 10% of the total transplants worldwide per year (Akoh, 2012). The present authors have previously reported that commercial transplant tourism accounts for almost 75% of RTX in Oman (Al Ismaili et al, 2017). In the present study, it was found that all of the commercial transplants in cases diagnosed with IFI were performed at various locations in Pakistan.…”
Section: Discussionsupporting
confidence: 48%
“…In Oman, despite finding no difference between the sexes in the incidence of ESKD (Al Ismaili et al, 2017), it was found that 54% of patients with ESKD who underwent renal replacement therapy were male (Al Ismaili et al, 2017). However, there is a slight predominance of males in overall transplant cases, and this difference between the sexes is even more pronounced in commercial cases, with males constituting 76.9% of such transplant recipients (Al Ismaili et al, 2017). This might be because of inherent cultural favoritism towards supporting males to obtain a transplant, as they are often considered the main breadwinner.…”
Section: Patientmentioning
confidence: 99%
“…The epidemiological transition of end-stage kidney disease in Oman was examined by using the End Stage Kidney Disease (ESKD) data from1983 to 2013 [12]. Data from 1998 to 2013 were obtained through an Information Management System.…”
Section: Status Of Hemodialysis In the Gulf Countriesmentioning
confidence: 99%
“…2,7 DN and CKD in Oman are increasing, and the health care expenditures are about 3.8-5.3 million Omani Riyals (OMR) per year for renal replacement therapy. 8 The kidney disease deaths in Oman reached 3.32% of the total deaths with the age-adjusted death rate estimated at 25.79 per 100,000 of population. 9 DN and CKD directly affects the quality of life and productivity and cause exhaustion of health care resource and financial stress.…”
Section: Introductionmentioning
confidence: 99%